Vente et rançonnement du butin humain des armées romaines à l’époque des conquêtes (264 av. J.-C. – 117 ap. J.-C.) - Jean-Christophe Robert (Les Cahiers de Framespa)
At the height of Roman imperialism, military victories brought in several millions of captives. Available figures show an increasing number of prisoners during the second half of the third century B.C. and until the first century B.C. The commander in chief had the power to sell prisoners as slaves. All captives were not sold, however, and the reviewers only mention, sometimes with figures, the most famous cases. During the public auction, captives were sold in batches, whose price was fixed in consideration of the value of some isolated specimens. These wholesale prices were necessarily lower than retail prices. Ransoming was the other way to take advantage of the captives. This practice was however rare and the sources only point out the cases of prestigious prisoners. The redemption of soldiers or whole defeated populations occurred during the Western wars and before the second century B.C. The amount of ransoms seems to have been roughly the same as the slaves’ prices.